IMPLEMENTING THE EXTRATERRITORIALITY PRINCIPLE TO STRENGTHEN COMPETITION LAW ENFORCEMENT IN INDONESIA IN THE AEC ERA: A COMPARATIVE STUDY - Wicaksono, Muhammad Rifky; Raditya, Kusuma; Andrini, Laurensia; Hawin, Muhammad (Indonesia Law Review, 2019)
The regional economic integration that ensues from the ASEAN Economy Community will provide its members not only with boundless opportunities for economic growth, but also with unprecedented challenges. The demands of a more interconnected regional economy would require the Indonesian government, as guardians of the competitive process in the Indonesian market, to protect it from anticompetitive conduct caused from both within and outside of its borders. However, there is a major gap since Indonesia’s current competition law does not provide KPPU with the jurisdiction to investigate, prosecute or punish violations committed by business actors located outside of Indonesia’s territory. Thus, this paper examines the implementation of the extraterritoriality principle to enable the KPPU and Indonesian courts to exercise jurisdiction over foreign business actors who violate Indonesia’s competition law from abroad. This paper employs a comparative approach to analyse the development of the extraterritoriality principle in US’, EU’s, Singapore’s and Malaysia’s competition law. This article concludes by determining how the extraterritoriality principle should be implemented to strengthen Indonesia’s competition law enforcement.